Nonparametric Regression Estimation for Circular Data - Andrea Meilán-Vila; Mario Francisco-Fernández; Rosa M. Crujeiras; Agnese Panzera (Proceedings, 2019)
Non-parametric regression with a circular response variable and a unidimensional linear regressor is a topic which was discussed in the literature. In this work, we extend the results to the case of multivariate linear explanatory variables. Nonparametric procedures to estimate the circular regression function are formulated. A simulation study is carried out to study the sample performance of the proposed estimators.